The Gospel of Mark: a commentary on the Greek text - France, Richard T. (The New international Greek Testament commentary, 2002)
Drawing on many years of Marcan studies, world-class scholar R. T. France has produced an exegetical commentary on the Greek text of Mark that does what the best of recent Greek commentaries have done but in France's own inimitable, reader-friendly way. This work is a commentary on Mark itself, not a commentary on commentaries of Mark. It deals immediately and directly with matters that France himself regards as important. Working from his own translation of the Greek text and culling from helpful research into the world of first-century Palestine, France provides an extensive introduction to Mark's Gospel, followed by insightful section and verse commentary. France sees the structure of Mark's Gospel as an effective "drama in three acts." Act 1 takes up Jesus' public ministry in Galilee. Act 2 covers Jesus' journey to Jerusalem with his disciples. Act 3 focuses on Jesus' public ministry in Jerusalem, including his confrontation with the Jewish leaders, his explanatory discourse on the future, and his passion, death, and resurrection. France carefully unpacks for modern readers the two central themes of this powerful narrative of Jesus' life - the nature of Christ and the role of discipleship. Supported by careful argumentation and impressive in its sensitivity to Mark's structure, context, and use of the Old Testament, France's study of the second Gospel is without peer.